2016
DOI: 10.1007/s00520-016-3458-x
|View full text |Cite
|
Sign up to set email alerts
|

Communication preferences of pediatric cancer patients: talking about prognosis and their future life

Abstract: Purpose-The American Academy of Pediatrics recommends that healthcare providers communicate information to patients in a truthful and developmentally appropriate manner. However there is limited guidance about how to translate these recommendations into clinical practice. The aim of this study was to explore how young cancer patients experienced communication around their illness, especially communication about possible outcomes from disease or treatment.Methods-Participants included young people ages 8 to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 28 publications
0
104
0
Order By: Relevance
“…46 Depending on adults for protection and difficult decisions Some participants, particularly young children, relied on their parents to "customize, clarify, or reiterate" 9 conversations with clinicians; advocate for their needs; and seek information on their behalf. 50 ).…”
Section: Reassured By Reliable Expertisementioning
confidence: 99%
See 2 more Smart Citations
“…46 Depending on adults for protection and difficult decisions Some participants, particularly young children, relied on their parents to "customize, clarify, or reiterate" 9 conversations with clinicians; advocate for their needs; and seek information on their behalf. 50 ).…”
Section: Reassured By Reliable Expertisementioning
confidence: 99%
“…24 Some wanted comprehensive data regarding therapeutic options; others felt safer knowing only "the basics" 9 as "bystanders." 21,41,46 Control over own life 21,41,46 Control over own life…”
Section: Right To Individual Knowledge and Choicementioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important as studies show discrepancies between adolescent patients, parents, and clinicians about the adolescent's desired extent of involvement in treatment‐related decisions . While it is possible that some clinicians may have previously discussed communication preferences with adolescents prior to the audio‐recorded conversations, we argue that clinicians should frequently reassess preferences and degree of desired involvement as these often change over time, and may be influenced by a patient's comfort with the medical environment, changing relationship with care team, state of health, growing maturity, and nature of the decisions to be discussed . We also found that the quality of adolescent response and overall engagement seemed to be influenced by the nature of clinician prompting.…”
Section: Discussionmentioning
confidence: 81%
“…Most pediatric patients want information provided to them by their healthcare provider and desire to directly participate in medical conversations . Additionally, most adolescent and young adults with cancer value receiving prognostic information, which is positively associated with aspects of well‐being . However, pediatric and adolescent patients displayed some ambivalence or endorsed conflicting wishes for prognostic information .…”
Section: Broaching the Discussion And Determining Participantsmentioning
confidence: 99%